2010
DOI: 10.1194/jlr.r001131
|View full text |Cite
|
Sign up to set email alerts
|

Rescue and repair during photoreceptor cell renewal mediated by docosahexaenoic acid-derived neuroprotectin D1

Abstract: This article is available online at http://www.jlr.org RETINAL DEGENERATIVE DISEASESRetinal degenerative diseases are a complex group of conditions with different etiologies that result in a common outcome: photoreceptor apoptotic cell death ( 1-5 ). Accordingly, there are differences in how these conditions evolve. For instance, in retinitis pigmentosa (RP), rod photoreceptor death initially occurs in the periphery, whereas in age-related macular degeneration (AMD), death is initiated in the macular zone and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
137
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(139 citation statements)
references
References 97 publications
0
137
0
2
Order By: Relevance
“…Excessive lipofuscin in the RPE of Abca4Ϫ/Ϫ mice, a model for STGD1, appears to result from a lack of N-retinylidene-PE flippase activity of the ABCA4 protein in the disk membrane rims (39). Alternatively, it is possible that VLC-PUFAs perform a direct signaling function: Bazan et al (40) have proposed that lipid molecules, such as DHA, serve as a special class of signaling molecules that activate specific receptors. Kahn-Kirby et al (41) have reported that eicosapentaenoic acid and arachidonic acid can modulate transient receptor potential cation channel activity and modulate olfactory and nociceptive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive lipofuscin in the RPE of Abca4Ϫ/Ϫ mice, a model for STGD1, appears to result from a lack of N-retinylidene-PE flippase activity of the ABCA4 protein in the disk membrane rims (39). Alternatively, it is possible that VLC-PUFAs perform a direct signaling function: Bazan et al (40) have proposed that lipid molecules, such as DHA, serve as a special class of signaling molecules that activate specific receptors. Kahn-Kirby et al (41) have reported that eicosapentaenoic acid and arachidonic acid can modulate transient receptor potential cation channel activity and modulate olfactory and nociceptive behavior.…”
Section: Discussionmentioning
confidence: 99%
“…10S,17S-DiHDHA has been measured in murine peritonitis but is produced only in trace quantities by human neutrophils (24 ). PD1 has potent immunoregulatory and neuroprotective actions (25 ) and is generated by isolated human leukocytes and tissues (24 ) and in particular by neural tissues where it is referred to as NPD1 (25 ). It is antifibrotic in the kidney and promotes wound-healing capacity (8 ).…”
Section: Discussionmentioning
confidence: 99%
“…These papers have reported on several docosanoids called protectins, resolvins and maresins (reviewed in 29 & 30). One of them, protectin D1, has also been named neuroprotectin D1 because of its specific action on neuron cells (31). Based on these data, we have reconsidered the possibility of making a double lipoxygenation product of DHA able to inhibit platelet aggregation.…”
Section: Lipoxygenation Of Dha and Effect Of The End-products On Platmentioning
confidence: 99%